Inquiry-Based Instruction in Science and Mathematics in Middle School Classrooms: Examining Its Association With Students' Attitudes by Gender and Race/Ethnicity. (August 2019) - Riegle-Crumb, Catherine; Morton, Karisma; Nguyen, Ursula; Dasgupta, Nilanjana
Utilizing a nationally representative sample of middle school students, this article focuses on whether students who report experiencing more inquiry-based instruction in science and mathematics classrooms have more positive attitudes toward these subjects. Results of multilevel, multivariate regression analyses revealed that, net of the inclusion of control variables for student, teacher, and school characteristics, a higher frequency of inquiry-based instruction is significantly associated with greater interest, perceptions of utility, and self-efficacy for science and mathematics. Furthermore, although there is some evidence indicating that compared with female students, male students' perceptions of science utility are higher in relation to more inquiry-based instruction, overall, the weight of evidence clearly leans toward the conclusion that the attitudes of students from different gender and racial/ethnic backgrounds are similarly associated with greater exposure to inquiry-based instruction in both their science and mathematics classrooms.